A Regularity Criterion for the Navier-Stokes Equations in the Multiplier Spaces - Xiang'ou Zhu (Abstract and Applied Analysis)
We exhibit a regularity condition concerning the pressure gradient for the Navier-Stokes equations in a special class. It is shown that if the pressure gradient belongs to 𝐿2/(2−𝑟)̇𝐻((0,𝑇);ℳ(𝑟(ℝ3̇𝐻)→−𝑟(ℝ3))), where ̇𝐻ℳ(𝑟(ℝ3̇𝐻)→−𝑟(ℝ3)) is the multipliers between Sobolev spaces whose definition is given later for 0<𝑟<1, then the Leray-Hopf weak solution to the Navier-Stokes equations is actually regular.